Conceptos actuales en la preparación de la cavidad apical para obturación retrógrada en cirugía perirradicular - Sivieri-Araujo, Gustavo [UNESP]; Chavez-Andrade, Gisselle M.; Tanomaru, Juliane Maria Guerreiro; Tanomaru Filho, Mario [UNESP] (My University, 2013)
The endodontic surgery is indicated in cases of failure and/or impossibility of conventional endodontic treatment. Among the existent modalities in the endodontic surgery, the retrograde filling consists on preparation of apical cavity and filling with a retrofilling material. The technical-scientific progress in Endodontics become possible the use of retrotips activated with ultrasonic for retrocavities preparation with appropriate extension and following the long axis of the root. The aim of the study was to present the current resources in the preparation of the retrograde cavity in endodontic surgery, detaching their advantages in comparison with the use of conventional preparation with burns. A review of the literature will be presented, considering the use of ultrasound and laser for retrograde preparation, seeking the current resources that provide better apical preparation, resulting in better prognostic of the endodontic surgery (AU)

La cirugía perirradicular está indicada en casos de fracaso del tratamiento endodóntico convencional y/o cuando no es posible realizarlo. Entre las modalidades existentes, la obturación retrógrada consiste en preparar y obturar la cavidad apical con materiales llamados de retroobturadores. La evolución técnica y científica de la endodoncia posibilita la utilización de puntas ultrasónicas, las cuales han facilitado la confección de retrocavidades con extensión adecuada y siguiendo el eje longitudinal de la raíz. El objetivo del presente estudio es presentar los recursos actuales respecto a la preparación de la retrocavidad en la cirugía perirradicular, destacando sus ventajas y comparándola con el empleo de la preparación convencional con el uso de fresas. Será presentada una revisión de la literatura, considerándose el empleo de ultrasonido y láser para preparación retrógrada, buscando recursos actuales que ofrezcan una mejor preparación apical y por consiguiente, mejorando el pronóstico de las cirugías periapicales (AU)
Modern concepts on the apical cavity preparation in retrograde filling